The Activating Role of Welfare Institutions and the Voices of the Youth in Transition from School to Work - Virva Leppänen (Social Work & Society, 2014)
This paper introduces the transition phase of the young people from school to work and the social policies designed to facilitate this transition. The emphasis is on the opportunities, constrains and challenges as posed by the welfare institutions on the agency of low qualified unemployed youth. In addition, the theoretical part of the paper includes an overlook on the discourses reproduced around young participants in a welfare measure as implied by Active Labour Market Policies (ALMP's) in Switzerland. These discourses are viewed against the evaluative and normative frame of the capability approach (CA) with specific focus on aspirations, autonomy and voice of the participants. The results derived from analysis based on interviews and observational measures imply adaptation of young people's aspirations to the labour market and the essential role of work for their self-definition, which further imply a focus on employability as a supply - side intervention of welfare policies.